Variabel-Variabel yang Mempengaruhi Persentase Tenaga Kerja Informal Gen Z di Indonesia Tahun 2021-2023 - Putri, Syofmarlianisyah; Achmad Prasetyo (Jurnal Ketenagakerjaan, 2025)
Indonesia, as the fourth most populous country in the world, has great human resource potential to drive economic growth. Based on BPS data, around 69.5% of Indonesia's population is of productive age, which also increases the number of workforce every year. However, limitations in providing formal employment can cause some of the workforce, including Gen Z, to be absorbed into the informal sector. Although the informal sector has continued to grow in recent years, this sector is still faced with a number of problems, such as low wages, minimal social protection, and the dominance of low-educated workers. This study focuses on the period 2021–2023, namely the post-COVID-19 pandemic recovery period marked by the acceleration of digitalization in the world of work. The purpose of this study is to analyze the variables that influence the percentage of Gen Z informal workers in Indonesia. Using data sourced from BPS and the Ministry of Manpower, the FEM SUR method was produced on a panel of data from 34 provinces. It was found that the variables of average length of schooling, income, internet, certified training, provincial minimum wage, and GRDP per capita had a significant negative influence on the percentage of informal workers of Gen Z.. This finding suggests that improving the quality of education and economic support can drive Gen Z towards more formal and protected jobs.